Study of the heat loss of an individual house built with the use of local thermal insulation materials - Kresava, Alena V.; Kuzhelka, Dzmitrij Yu.; Kundas, Sjamjon P. (Journal of the Belarusian State University. Ecology, 2018)
Application of new insulating materials requires research for their efficiency, especially if these materials are used in multilayer structures. This work was focused on the study of environmentally friendly local materials for individual building insulation, under the directions of local community’s sustainable development. This was done to help decrease housing construction cost, energy consumption and greenhouse gas emissions, and is currently under development in Belarus. The aim of this work is to analyze the efficiency of local insulating material usage with the use of computer simulation methods. Numerical 3D models were developed in the software packages using SolidWorks and COMSOL Multiphysics. Experimental thermography measurements were also completed for insulating efficiency analysis of local environmental friendly material. Numerical analysis and thermographic measurement was performed for framework type homes with the following thermal insulation envelopes: 1) reed; 2) reed and clay + straw; 3) reed + ecowool + flax fibers; 4) brick (as reference material). The resulting measurements and numerical calculation had shown the effectiveness of using these materials for insulation in comparison with traditional brick constructions.